2012
DOI: 10.3109/17483107.2012.667194
|View full text |Cite
|
Sign up to set email alerts
|

Impact of assistive technology on family caregivers of children with physical disabilities: a systematic review

Abstract: Evidence suggests that AT has a positive impact on children with physical impairments and their caregivers. Future studies in this area could include valid and reliable outcome measures of AT use and the psychological impacts of AT on caring for a child with physical impairments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 13 publications
2
37
0
1
Order By: Relevance
“…This qualitative synthesis builds on the findings of previous systematic reviews . Nicolson et al . called for more research describing the impacts on family caregivers of children with physical disabilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This qualitative synthesis builds on the findings of previous systematic reviews . Nicolson et al . called for more research describing the impacts on family caregivers of children with physical disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of power mobility outcomes for children identified, but did not include, a significant number of qualitative studies relating to the child's and family's perspective, and it was recognized that a separate, more appropriate, analysis was warranted. Three previous systematic reviews on children's use of assistive technologies included only two qualitative studies on power mobility use …”
mentioning
confidence: 99%
“…Included in the stories they relayed were themes of guilt, conflict, exhaustion and a sense of working in isolation, all of which have been reported in previous studies. 48,52 In addition, they expressed concerns about the way therapies intruded into their child's life and prevented the child from doing other activities. They also described their children's responses to receiving therapy.…”
Section: The Practice Of Therapiesmentioning
confidence: 99%
“…[48][49][50][51] Notions of feeling overburdened by the requirements of a therapy regime, and a lack of ongoing training and support, have also been reported. 52 In terms of work within the existing NIHR portfolio, a study 47 funded as part of the Research for Patient Benefit programme has been recently published, which evaluated a training intervention for parents and school staff on postural management. Different models for organising therapy provision were reported, and alternatives to the traditional model of 'unitherapy' teams were presented.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Moir [11] found insufficient validated, reliable and sensitive assessment tools to measure switch use in children with physical and multiple disabilities. Nicolson et al [12] suggested that greater quantitative research, in the field of assistive technology, is needed which uses reliable and valid outcome measures. Isabelle et al [4] suggests that the reason behind the lack of research using valid and reliable measures is simply a lack of reliable and valid tools in existence which is supported by Silverman and Smith [13] who also identify a lack of valid assessment tools.…”
Section: Introductionmentioning
confidence: 99%